1994
DOI: 10.1016/0550-3213(94)90521-5
|View full text |Cite
|
Sign up to set email alerts
|

The electric charge of neutrinos and plasmon decay

Abstract: By using both thermal field theory and a somewhat more intuitive method, we define the electric charge as well as the charge radius of neutrinos propagating inside a plasma. We show that electron neutrinos acquire a charge radius of order ∼ 6.5 × 10 −16 cm, regardless of the properties of the medium. Then, we compute the rate of plasmon decay which such an electric charge or a charge radius implies. Taking into account the relativistic effects of the degenerate electron gas, we compare our results to various a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 43 publications
1
33
0
Order By: Relevance
“…This effective vertex is due to the W and Z in the loops in the Feynman diagram [3,8]. The vertex tensor is gauge invariant quantity, as k µ Γ αµ = 0 [3,8]. The effective vertex tensor is [8] …”
Section: Cerenkov Processmentioning
confidence: 99%
See 3 more Smart Citations
“…This effective vertex is due to the W and Z in the loops in the Feynman diagram [3,8]. The vertex tensor is gauge invariant quantity, as k µ Γ αµ = 0 [3,8]. The effective vertex tensor is [8] …”
Section: Cerenkov Processmentioning
confidence: 99%
“…that neutrino acquires an effective charge in the medium by coupling to the electromagnetic field through electrons and positrons in the plasma [2,3].…”
Section: Cerenkov Processmentioning
confidence: 99%
See 2 more Smart Citations
“…[10]. And, it has also been shown that the ν − γ interaction in presence of a thermal medium induces a small effective charge to the neutrino and that the neutrino electro-magnetic vertex is related to the photon self-energy in the medium [11,12]. Recently, this effective charge has been calculated, considering not only a thermal medium but also an external magnetic field, for neutrinos coupled to dynamical photons having q 0 = 0 and | q| → 0 [13].…”
Section: Introductionmentioning
confidence: 99%